DIDACTIC MODEL OF TEACHING COMPUTER LINGUISTICS - Mamirov Ozodjon (Web of Journals Publishing, 2023)
One of the important requirements for the organization of modern education today is to achieve high results in a short time without spending too much mental and physical effort. For this, the teacher requires high pedagogical skills and a new approach to the educational process. A lot of theoretical advice has been developed on the issue of educating a creative person, but today the teacher needs clear instructions on how to organize the independent work of students in the formation of independent learning skills.